Influenciadoras digitais: a mulher discursivisada em enunciados de moda e beleza no Instagram - Terence Silva, Tainá (2020)
The outset of Web 2.0 and its technological advances allowed interpersonal relationships and knowledge production happens in decentralized by different possibilities, as social media apps, for example. Therefore, by studying a specific social media that is Instagram, this work aims to investigate how beauty discourse is built-in posts of the 10 most remarkable digital influencers in Brazil by the year 2018. Thus, the guiding research question is "How beauty discourse for/to the woman it is set up at Instagram's posts of the most prominent fashion and beauty digital influencers of Brazil?". For that matter, these posts were analyzed taking the images as statements with the view to observe discursive regularities that built significance to and for a woman's body. Those statements were separate into eight categories namely as i) hands' positions: face or hair, ii) hands' position: hips, iii) bodies in union with other bodies, iv) marked body, v) body: the face in question, vi) body absence, viii) commercialized body and viii) body in movement. Hence, it follows a theoretical-methodological line defended by French Discourse Analysis with basal recurrences to Michel Foucault's studies, as well as historical studies about beauty. The corpus is compound by 60 posts that are illustratively analyzed by a thematic path observing regularities about a woman's body and recurrences of a corporal beauty pattern that starts to be expressive by 1990. Thereby, the study shows the construction of an established meaning for the beauty, named as Discursive Formation- ID (FD-ID), that relies on a discursivized body understand by a consume beauty and an aestheticization of subjectivity. Furthermore, it was possible to established historicity with fashion magazine covers, product ads, brand clothes croquis, and sketches starting by the year 1950. The observation of those data, combined with the statements from the IDs, shows the existence of a historical interlacement that confirms the emergence of this beauty discourse that it’s also possible to see in operation at social media.